2007
DOI: 10.1158/1078-0432.ccr-06-2476
|View full text |Cite
|
Sign up to set email alerts
|

Promoter Hypermethylation Identifies Progression Risk in Bladder Cancer

Abstract: Purpose: New methods to accurately predict an individual tumor behavior are urgently required to improve the treatment of cancer. We previously found that promoter hypermethylation can be an accurate predictor of bladder cancer progression, but it is not cancer specific. Here, we investigate a panel of methylated loci in a prospectively collected cohort of bladder tumors to determine whether hypermethylation has a useful role in the management of patients with bladder cancer. Experimental Design: Quantitative … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
135
1
4

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(152 citation statements)
references
References 26 publications
12
135
1
4
Order By: Relevance
“…These data suggest that transient activation of ZEB proteins triggers EMT, but its maintenance in growing tumors may require additional, possibly epigenetic mechanisms. This is in agreement with the notion that DNA methylation is involved in transcriptional silencing of E-cadherin gene in bladder cancer cell lines and in tumor tissues (26).…”
Section: Discussionsupporting
confidence: 92%
“…These data suggest that transient activation of ZEB proteins triggers EMT, but its maintenance in growing tumors may require additional, possibly epigenetic mechanisms. This is in agreement with the notion that DNA methylation is involved in transcriptional silencing of E-cadherin gene in bladder cancer cell lines and in tumor tissues (26).…”
Section: Discussionsupporting
confidence: 92%
“…Epigenetic predictive models using artificial intelligence also support the premise that promoter hypermethylation is a reliable predictor of tumor progression in bladder cancer. 29 Collectively, these data support the concept that cigarette smoke is not only a direct mutagenic carcinogen, but also associated with the genesis of epigenetic alterations in bladder cancer. 30 Continuous tobacco carcinogen exposure, in combination with increasing age and male gender, drives and enhances the selection and clonal expansion of epigenetically altered cells.…”
Section: Bladder Cancer Carcinogenesissupporting
confidence: 61%
“…Yan et al 24 , showed that methylation of RUNX3 in combination with G3 increased the chance of disease progression. According to Yates et al 15 , methylation of E-cadherin, TNFRSF25, EDNRB, RASSF1A, and APC were significantly associated with progressive disease. Yet, these studies all used a mixture of pT1 and pTa tumors.…”
Section: Discussionmentioning
confidence: 97%
“…[13][14][15] Recently, Kandimalla et al 16 studied genome-wide hypermethylation of CpG islands in association with tumor progression. They investigated 238 unique CpG islands in pTaG1/2 tumors with and without disease progression, ie progression to muscle-invasive disease, metastasis or dead of disease.…”
mentioning
confidence: 99%